2006
DOI: 10.30843/nzpp.2006.59.4550
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide timing for the control of septoria tritici blotch of wheat

Abstract: A field trial during the 200506 growing season used different fungicides and timing of fungicide applications to manipulate the development of Septoria tritici blotch on artificiallyinoculated wheat (cv Consort) Disease severity was assessed once or twice a week and the area under the disease progress curve (AUDPC) calculated The fungicide azoxystrobin applied at the prestem extension stage of crop growth had the lowest AUDPC and provided the best level of protection against the disease on the top three leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Savannah in 2014. General pathology Results also showed prothioconazole was more effective at 50-100% label than epoxiconazole, which is consistent with Marroni et al (2006) where epoxiconazole was less effective at controlling initial infection. There was a yield advantage with high rates of triazole application, but 25% label rates of epoxiconazole offered no yield advantage compared to the untreated.…”
Section: Figuresupporting
confidence: 76%
See 1 more Smart Citation
“…Savannah in 2014. General pathology Results also showed prothioconazole was more effective at 50-100% label than epoxiconazole, which is consistent with Marroni et al (2006) where epoxiconazole was less effective at controlling initial infection. There was a yield advantage with high rates of triazole application, but 25% label rates of epoxiconazole offered no yield advantage compared to the untreated.…”
Section: Figuresupporting
confidence: 76%
“…This work has mirrored that in the United Kingdom of Fraaije et al (2007). Previously farmers could grow STB susceptible cultivars and protect them with fungicides (Brown 2012), even though more resistant cultivars were available (Marroni et al 2006).…”
Section: Discussionmentioning
confidence: 76%
“…While epoxiconazole suppresses Z. tritici growth it is less effective than some other fungicides. For example, both Marroni et al (2006) and Godwin et al (1994) found epoxiconazole did not inhibit the early stages of a Z. tritici infection as much as azoxystrobin (assuming a sensitive strain of the pathogen).…”
Section: Samplesmentioning
confidence: 98%
“…Anon., ). The response of wheat to the timing of plant growth regulators (Kettlewell et al , ; Bodson & Durdu, ; Gandee et al , , ; Rajala & Peltonen‐Sainio, ; Hussain & Leitch, ; Wiersma et al , ; Huberman et al , ; Peng et al , ), herbicides (Wilson & Cussans, ; Tottman, ; Martin et al , ; Leaden et al , ; Pageau & Lajeunesse, ; Kong et al , ; Robinson et al , ), insecticides (Carter et al , ; Mann et al , ; Oakley et al , ; Kennedy & Connery, ), fungicides (Nelson & Sutton, ; Cook & Hayward, ; Guy et al , ; Goulds & Fitt, ; Duczek & Jones‐Flory, ; Cook et al , ; Nicolas, ; Wiersma & Motteberg, ; Marroni et al , ; Edwards & Godley, ; Wegulo et al , ) and nitrogen application (Darwinkel, ; Powlson et al , ; Sylvester‐Bradley et al , ; Maidl et al , ; Sticksel et al , , ; Flowers et al , ; Weisz et al , ; Efretuei et al , ) are all commonly interpreted with reference to DGS. Similarly, the responses to other agronomic decisions, such as sowing density, can be interpreted with reference to canopy formation and architecture at particular DGS (Whaley et al , ).…”
Section: Growth Stage Scores Defining Cereal Developmentmentioning
confidence: 99%